Identification of Plant Species Diversity at SMAN 1 Nguter as Source of Learning Based on Local Potential - Umi Salamah; Hidayatun Nurul Khasanah; Suwarto Suwarto; Pardi Pardi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Learning biology directly in the environment provides experiences for students so they can develop an interest in biology. Local potential can be used as a source of learning biology. Biology material has not been linked much in everyday life and is fixated on books. Some biology teachers are less sensitive to the potential in the environment. The solution is to combine biological materials with local potential. The purpose of this article is to identify local potential at SMA N 1 Nguter as a source of learning biology based on local potential on biodiversity material and a form of integrating local potential into biodiversity material. This type of research uses qualitative. As well as an inventory of local plants along with their morphological characteristics using observation and interview methods as well as the types of flowers, the classification is written down. Based on the results of the study, the local potential of flower plants at SMA N 1 Nguter has 5 types of flowers with 12 kinds of colors that can be used as a source of learning biology based on local potential. The form of integrating the potential of flower plants on biodiversity material at the gene and species level can be arranged in modules.